2015
DOI: 10.1186/s12941-015-0067-3
|View full text |Cite
|
Sign up to set email alerts
|

Screening of antimicrobial, antioxidant properties and bioactive compounds of some edible mushrooms cultivated in Bangladesh

Abstract: BackgroundFor a long time mushrooms have been playing an important role in several aspects of the human activity. Recently edible mushrooms are used extensively in cooking and make part of new food in Bangladesh for their beneficial properties. The aim of this study is to screen some values of mushrooms used in Bangladesh.MethodsMethanolic extracts of 3 edible mushrooms (Pleurotus ostreatus, Lentinula edodes, Hypsizigus tessulatus) isolated from Chittagong, Bangladesh were used in this study. Phenolic compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
41
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 29 publications
15
41
2
Order By: Relevance
“…Similarly, a previous study has also reported antimicrobial activity from the extract of mushrooms [7]. In our study, the maximum inhibition zone was shown by Pleurotus pulmonarius (BPSM36) showing antibacterial activities against P .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similarly, a previous study has also reported antimicrobial activity from the extract of mushrooms [7]. In our study, the maximum inhibition zone was shown by Pleurotus pulmonarius (BPSM36) showing antibacterial activities against P .…”
Section: Discussionsupporting
confidence: 81%
“…Worldwide, they are well recognized as supplementary food due to their high nutritional values [1, 2] and medicinal importance, which includes their antioxidant and antimicrobial activities [3, 4], immune enhancer [57], and to be effective for the treatment of diabetic [8, 9] and few types of cancers as well [10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…These findings are thought to be the consequence of using acidic water (Nakano et al, 2000) for preparing mushroom extracts, as we did in this study; this method may not be suitable for extracting tannins or other phenolic compounds of some mushroom species (Tiwari et al, 2011). We did find flavonoids in most of the mushroom extracts; this finding supported the presence of catechin in shitake mushroom, log white fungi, and log black fungi (Attarat and Phermthai, 2015;Chowdhury et al, 2015). Some studies have demonstrated that bioactive compounds in mushrooms play an essential role in the human immune system by acting as immunomodulating molecules.…”
Section: Discussionsupporting
confidence: 65%
“…S. aureus ATCC 6588 was found to require an extract concentration of 12.5 mg/mL, regardless of the source of nitrogen used for the occurrence of high antimicrobial activity, and E. coli CBAB 2 proved to be resistant to these extracts. The mycelial hotwater extract evaluated here was also effective at a concentration lower than MICs reported for a methanolic extract of P. ostreatus isolated from Bangladesh, in the range of 4 mg/mL for the yeasts C. albicans and S. cerevisiae to 8 mg/mL for P. aeruginosa (Chowdhury, Kubra, & Ahme, 2015).…”
Section: Antimicrobial Activity Of Pleurotus Sp Hot-water Mycelial Ementioning
confidence: 93%